2005
DOI: 10.1159/000089678
|View full text |Cite
|
Sign up to set email alerts
|

Combination Chemotherapy in Advanced Small Bowel Adenocarcinoma

Abstract: Objective: To assess the efficacy of 5-fluorouracil (5-FU) and either platinum compounds or irinotecan in patients with advanced small bowel adenocarcinoma (SBA), for whom data on the efficacy of chemotherapy are scarce. Methods: We reviewed data on all patients with advanced SBA who received chemotherapy over a 9-year period at our institution. Results: Twenty patients with advanced SBA received a median of 6 cycles (range 2–15) of chemotherapy with 5-FU and either cisplatin (n = 15), carboplatin (n = 2), or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 33 publications
(31 reference statements)
3
52
0
3
Order By: Relevance
“…Fluoropyrimidines are generally considered to be the key drugs for SBA and other gastrointestinal cancers. Most regimens used in previously reported studies of chemotherapy for unresectable SBA included fluoropyrimidines; to date, there has been no active regimen without these drugs [11][12][13][14][15][16][17][18][19][20][21][22][23]. However, no prospective or retrospective study has clearly showed advantages of a combination regimen compared with fluoropyrimidine monotherapy for unresectable SBA with regard to PFS or OS times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluoropyrimidines are generally considered to be the key drugs for SBA and other gastrointestinal cancers. Most regimens used in previously reported studies of chemotherapy for unresectable SBA included fluoropyrimidines; to date, there has been no active regimen without these drugs [11][12][13][14][15][16][17][18][19][20][21][22][23]. However, no prospective or retrospective study has clearly showed advantages of a combination regimen compared with fluoropyrimidine monotherapy for unresectable SBA with regard to PFS or OS times.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorouracil (5-FU) is the most commonly used agent for the treatment of unresectable or recurrent SBA, and various 5-FU based regimens have been used [11][12][13][14][15][16][17][18][19][20][21][22][23]. In a retrospective analysis, Overman et al reported that combination therapy with 5-FU and platinum compounds showed more favorable results than other regimens [21].…”
Section: Introductionmentioning
confidence: 99%
“…Several phase II studies examining a variety of protocols with different OS have been published [21][22][23][24][25]. There are also retrospective single centre experiences comparing different regimens [5,15,16,20,[26][27][28][29][30]. Current expert opinion favors use of a fluoropyrimidine-platinum combination in the first line [20,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…To date, no reports have described SBA patients treated with IP as fi rst-line chemotherapy. Polyzos et al [7] reported that two of three patients with advanced SBA achieved PR and palliation of symptoms with single-agent irinotecan, while Locher et al [6] found that second-line chemotherapy with 5-FU and irinotecan resulted in disease stabilization in 50% of patients. Fishman et al [13] retrospectively reported that a chemotherapy regimen including irinotecan appeared to offer higher overall response rates than fl uorouracil-based regimens for fi rst-or second-line chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Erlichman et al [14] reported that, in a phase I study, combination treatment with irinotecan, 5-FU, leucovorin, and oxaliplatin resulted in one partial response and two patients with SD. Also, Locher et al [6] found that combining 5-FU and platinum compounds for fi rst-line chemotherapy resulted in an objective response rate of 21%, a median progression-free survival of 8 months, and median overall survival (OS) of 14 months, with manageable toxicities.…”
Section: Discussionmentioning
confidence: 99%